ANALISIS PENGARUH DORONGAN BERPRESTASI DAN PENGAKUAN TERHADAP KOMPETENSI APOTEKER DALAM MENGELOLA APOTIK - Edi Sukarjono (Universitas Pamulang, 2015)
ANALYSIS OF EFFECT OF ENCOURAGEMENT ACHIEVEMENT AND RECOGNITION OF COMPETENCE MANAGING PHARMACIST IN PHARMACY. This research is an activity to determine the factors that affect the competence of pharmacists that have implications for the performance of pharmacists in pharmacy management. The research objective was to examine and analyze the magnitude of the following research variables: (1) Condition: encouragement of achievement and recognition, from the pharmacist. (2) The condition of Pharmacists competence. (3) How much influence: encouragement of achievement and recognition of the competence of pharmacists pharmacists partially. (4) How much influence the encouragement of achievement and recognition of the competence of pharmacists simultaneously. The research is quantitative research, described in the descriptive analysis and verification and performed in Banten province, with a sample of 151 pharmacists who practice at least 30% of the number of days open from pharmacies. The sampling technique used proportionate stratified random sampling, to differentiate samples by length of work diapotik with a span of <3 years, 4-6 years, 7-10 years and> 10 years. Data analysis method used is path analysis. The results showed that respondents: (1) Conditions encouragement of achievement and recognition of Pharmacists in the stage quite well until very good. (2) The condition of Pharmacists competence in the stage quite well until very good. (3) There is a significant and positive influence of encouragement and recognition of achievement 8.40% at 34.70% (5) There is a significant influence on the encouragement of achievement and recognition of the competence of the simultaneous 41%. Keywords: the encouragement of achievement and recognition, responsibility and work attitudes, perceptions and moral work, competence, performance pharmacist.